Comparative Analysis of Thermohydraulic Properties of Nano-Refrigerants - Parkash, Jai; Saini, Sanjeev; Kohli, Ankush; Singh, Balkar (International Journal of Engineering and Technology, 2018)
The nano-particles achieved the focus of the researchers in the field of refrigeration, due to its capability to change the properties of refrigerants upto a large extent. Nanofluids based on refrigerant is known as nano refrigerants and provided an improvement in thermophysical properties of various refrigerants in different terms. Different theoretical and experimental models are provided by the researchers have been used for the evaluation of different properties of refrigerant in terms of thermal conductivity, density, specific heat and viscosity of the refrigerants. In this effort, a number of models, and correlations have been used to result in the improvement in these properties of nano refrigerants. This is achieved by the addition of nanoparticles with varying volume concentration of 1% to 5 %. The analyses have been made within a temperature range of 190K- 269K at a constant pressure of 0.3 MPa. The study is elaborated to compare the various refrigerants which are R11, R12, R22, R134a and R141b with the addition of different nano-particles which are TiO2, Al2O3, ZnO and CuO at evaporator conditions. The addition of ZnO has given a good impact on the thermal conductivity of refrigerants. Effective viscosity of nano refrigerants depends upon the viscosity of refrigerants and volumetric concentration of nano-sized particles. Specific Heat shows the negative variation with the addition of nanoparticles but increased with the rise in temperature. The density of nano refrigerants depends upon the density of base refrigerant, Density of nanoparticles, volumetric concentration of nanoparticles. In future, the study can be elaborated in terms of compressor work, power consumption and overall performance of refrigeration system.Â Â